Editorial to the HELINA 2023 Proceedings - Mostert, Nicky (Journal of Health Informatics in Africa, 2024)
The 2023 edition of the HELINA (HEaLthINformaticsinAfrica) conference was held from 01 – 03 November 2023 as an in-person conference in Cape Town, South Africa. The conference was hosted by the South African Health Informatics Association (SAHIA) in partnership with HELINA. The conference theme was focused on “Effective Implementation, Meaningful Use and Sustainability of Digital Health Interventions: The Role of Health Informatics and Imaging Informatics in Africa”. The aim was to provide a platform to showcase interventions in the following formats: • Full research papers based on mature research results; • Work in progress papers based on work in process research; and • Case study presentations based on case studies and experience in digital health interventions. Review Process A total of 61 submissions in these categories were received. A double-blind peer review process was used for evaluating each full research and work in progress paper. These submissions were anonymized before being submitted to reviewers according to their area of expertise. The Scientific Programme Committee (SPC) based their final decision on the acceptance of each full research and work in progress paper on the recommendations and comments from reviewers. Accepted submissions were then sent back to the authors for revision according to the reviewers’ comments. Case study submissions were reviewed by the SPC for inclusion in the conference. This review process resulted in the following acceptance rates: • Full research papers: 44% acceptance rate (9 received, 4 accepted) • Work in progress papers: 66% acceptance rate (6 received, 4 accepted) • Case studies and experience papers: 85% acceptance rate (46 received, 39 accepted) In order to be included in the conference proceedings, authors had to submit their final camera-ready papers after incorporating reviewer comments, and accepted papers had to be presented at the conference in person. Nicky Mostert HELINA 2023 SPC Chair